On field vaccine effectiveness in three periods of 2018/2019 influenza season in Emilia-Romagna Region - Colucci, Maria Eugenia; Veronesi, Licia; Bracchi, Maria Teresa; Zoni, Roberta; Caruso, Luca; Capobianco, Emanuela; Rossi, Deanna; Bizzarro, Assunta; Cantarelli, Angelo; Affanni, Paola (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: Epidemic influenza is associated with significant morbidity and mortality, particularly in people at risk. The vaccine reduces complications, hospitalization and mortality excess, as well as health care and social costs. Aim of the study was to estimate the influenza vaccine effectiveness (VE) in Emilia-Romagna Region during the 2018/2019 season. Methods: Within the context of virological surveillance conducted at the Regional Reference Laboratory of Parma, nasal/throat swabs were performed by sentinel practitioners and clinicians, on patients with ILI (Influenza-like illness). VE estimates, overall and against subtype A(H1N1)pdm09 and A(H3N2), were evaluated in three periods of the season, using a test-negative case-control design. Results: From November 2018 to April 2019, 2,230 specimens were analyzed: 1,674 (75.1%) performed by clinicians and 556 (24.9%) by sentinel practitioners of the regional network. The season was characterized by the predominant circulation of influenza type A viruses: 57.4% belonged to subtype A(H3N2), 41.2% to subtype A(H1N1)pdm09. 23.5% of patients was vaccinated against influenza with quadrivalent or adjuvate vaccine. The overall VE was -5% (95% CI -33% - 18%) with a decreasing trend during the season. The overall VE against subtype A(H1N1)pdm09 was 39% (95% CI 11% - 58%) and remained stable during the season. The overall VE against subtype A(H3N2) was -43% (95% CI -89% - -9%), and showed an important decreasing trend. Conclusions: The possibility to make accurate and continuous VE estimates during the season will help to better define the composition of the vaccine for the following season.